Relationship between Didactic Attendance and Average Ophthalmic Knowledge Assessment Program Performance - Altenbernd, Todd W. (Journal of Academic Ophthalmology, 2020)
Background The Accreditation Council for Graduate Medical Education's ophthalmology-specific program requirements indicate that a resident must participate in 360 hours of educational activities over the course of residency. The requirements allow a variety of options by which this educational process may occur. Furthermore, the current generation of learners has used a large array of learning tools in their careers: digital media, online resources, question banks, flipped classrooms, problem-based learning, and asynchronous lectures in addition to the traditional face-to-face didactic lectures.Objectives This article determines if the traditional face-to-face didactic lectures play a significant role in the education of ophthalmology residents, attempts to quantitate this role, and estimates the relative importance of this method.Methods Lecture hours beginning immediately after an Ophthalmic Knowledge Assessment Program (OKAP) examination and up to the subsequent exam was tabulated for 40 residents over 8 years. From 2012 through 2019 each of the residents took the OKAP exam one to three times. The average overall OKAP score for each resident was then regressed against his or her logged hours of didactics that year. This rate of average OKAP score to lecture hours was then evaluated for significant differences on the basis of postgraduate year (PGY). “STATA 13.1 IC,” was used for all statistical analysis.Conclusion Traditional synchronous didactic lectures play a statistically significant role in the education of ophthalmology residents. For each 3.5 hours of lectures per year there is a 1% increase in the average OKAP score, p = 0.0064. However, the amount of variability explained by this single factor is low, R2 = 0.067, and other factors are presumed to play a large part in learning. PGY subgroup analysis showed significant difference in the OKAP performance to lecture hour relationship, the number of lecture hours attended, and the OKAP performance.
Keywords: OKAP; Ophthalmic Knowledge Assessment Program; face-to-face lectures; traditional didactic lecture; resident education; synchronous learning; asynchronous learning; didactic lecture